Recommendations for mitochondria transfer and transplantation nomenclature and characterization - Brestoff, Jonathan R; Singh, Keshav K; Aquilano, Katia; Becker, Lance B; Berridge, Michael V; Boilard, Eric; Caicedo, Andrés; Crewe, Clair; Enríquez, José Antonio; Gao, Jianqing; Gustafsson, Åsa B; Hayakawa, Kazuhide; et al. (Nature metabolism, 2025)
Intercellular mitochondria transfer is an evolutionarily conserved process in which one cell delivers some of their mitochondria to another cell in the absence of cell division. This process has diverse functions depending on the cell types involved and physiological or disease context. Although mitochondria transfer was first shown to provide metabolic support to acceptor cells, recent studies have revealed diverse functions of mitochondria transfer, including, but not limited to, the maintenance of mitochondria quality of the donor cell and the regulation of tissue homeostasis and remodelling. Many mitochondria-transfer mechanisms have been described using a variety of names, generating confusion about mitochondria transfer biology. Furthermore, several therapeutic approaches involving mitochondria-transfer biology have emerged, including mitochondria transplantation and cellular engineering using isolated mitochondria. In this Consensus Statement, we define relevant terminology and propose a nomenclature framework to describe mitochondria transfer and transplantation as a foundation for further development by the community as this dynamic field of research continues to evolve.
Keywords: Mitochondria; terminologie jako téma; Animals; lidé; Terminology as Topic; Humans; zvířata; mitochondrie